(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The development of international trade relations and globalization processes has significantly increased the importance of translation in cross-border communication. Trade documents such as contracts, invoices, customs declarations, certificates, and financial agreements play a key role in regulating economic cooperation between countries. Since these documents combine legal and economic content, their translation requires high linguistic accuracy, terminological consistency, and professional knowledge.\